Quality management and accounting in a New Zealand service organization: Towards an institutional perspective on management accounting - Hoque, Zahirul; Alam, Manzurul (School of Management Working Papers, 1995)
Recently, the concept of quality and its management have received considerable attention from business organizations in countries around the world seeking to remain competitive in both local and international markets. Accounting researchers have become interested in understanding how accounting systems are implicated within a quality management system. This paper, which reports on the quality management systems in a New Zealand service organization, provides empirical evidence of how an organization adopts quality principles and subsequently evaluates organizational approaches to espouse quality as a strategic option and the role of accounting therein. The paper argues that once an organization introduces quality management, it may influence other aspects of an organization, such as accounting and reporting processes, to serve the managers’ need on quality issues. This paper suggests that quality management in the organization was "institutionally induced" as well as affected by the organizational climate and individuals’ quality-related behaviour.